Natural Variation in the Control of Flowering and Shoot Architecture in Diploid Fragaria Species - Fan, Guangxun; Andrés, Javier; Olbricht, Klaus; Koskela, Elli; Hytönen, Timo (Frontiers in Plant Science, 2022)
In perennial fruit and berry crops of the Rosaceae family, flower initiation occurs in late summer or autumn after downregulation of a strong repressor TERMINAL FLOWER1 (TFL1), and flowering and fruiting takes place the following growing season. Rosaceous fruit trees typically form two types of axillary shoots, short flower-bearing shoots called spurs and long shoots that are, respectively, analogous to branch crowns and stolons in strawberry. However, regulation of flowering and shoot architecture differs between species, and environmental and endogenous controlling mechanisms have just started to emerge. In woodland strawberry (Fragaria vesca L.), long days maintain vegetative meristems and promote stolon formation by activating TFL1 and GIBBERELLIN 20-OXIDASE4 (GA20ox4), respectively, while silencing of these factors by short days and cool temperatures induces flowering and branch crown formation. We characterized flowering responses of 14 accessions of seven diploid Fragaria species native to diverse habitats in the northern hemisphere and selected two species with contrasting environmental responses, Fragaria bucharica Losinsk. and Fragaria nilgerrensis Schlecht. ex J. Gay for detailed studies together with Fragaria vesca. Similar to F. vesca, short days at 18°C promoted flowering in F. bucharica, and the species was induced to flower regardless of photoperiod at 11°C after silencing of TFL1. F. nilgerrensis maintained higher TFL1 expression level and likely required cooler temperatures or longer exposure to inductive treatments to flower. We also found that high expression of GA20ox4 was associated with stolon formation in all three species, and its downregulation by short days and cool temperature coincided with branch crown formation in F. vesca and F. nilgerrensis, although the latter did not flower. F. bucharica, in contrast, rarely formed branch crowns, regardless of flowering or GA20ox4 expression level. Our findings highlighted diploid Fragaria species as rich sources of genetic variation controlling flowering and plant architecture, with potential applications in breeding of Rosaceous crops.